2010
DOI: 10.3892/ijo_00000750
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of docosyl p-coumarate on DNA topoisomerase activity and human cancer cell growth

Abstract: Abstract. We previously found six compounds of alkyl pcoumarates from a composite plant Artemisia annua L., and chemically synthesized these compounds (cis-isomer of C20, C22 and C24, and trans-isomer of C20, C22 and C24 of pcoumarates are compounds 1-6, respectively). This report describes the inhibitory activities of these alkyl p-coumarates against DNA polymerase (pol), DNA topoisomerase (topo), and human cancer cell growth. Among the compounds tested, compounds 1 and 4 weakly inhibited repair-related pol ß… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…Compounds 95, 97 and 93 and 96 were potent inhibitors of human topos I and II, respectively. They also suppressed HCT116 human colon carcinoma cell line growth, with or without p53 inhibition, suggesting that cell growth inhibition had the same tendency as the topos inhibition [59].…”
Section: Dna Topoisomerasesmentioning
confidence: 87%
“…Compounds 95, 97 and 93 and 96 were potent inhibitors of human topos I and II, respectively. They also suppressed HCT116 human colon carcinoma cell line growth, with or without p53 inhibition, suggesting that cell growth inhibition had the same tendency as the topos inhibition [59].…”
Section: Dna Topoisomerasesmentioning
confidence: 87%
“…However, in an in vitro experiment, ethanol extract of A. afra was cytotoxic against U937 and HeLa cancer cells via the decrease in mitochondrial membrane potential after G2/M arrest (Spies et al, 2013;Venables et al, 2016). Some Artemisia species and their active components that have been shown to arrest cells in in vitro experiments with cell lines include, A. sphaerocephala (Wang et al, 2017), A. princeps, cell cycle arrest at G2/M (Lee et al, 2013), A. monosperma, cell cycle arrest at S+G2/Mphase (Whelan and Ryan, 2004) and A. annua (Mizushina et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The PTPB inhibitory effect of samples was analyzed using the modified method of Burke et al [9]. A sample (3 μL in DMSO) was added to a reaction mixture containing 2 μL of 0.5 μg/mL enzyme, 10 μL of buffer (50 mM citrate, pH 6.0, 0.1 M NaCl, 1 mM EDTA, and 1 mM dithiothreitol), 35 μL of water, and 50 μL of 20 mM phosphatase substrate.…”
Section: Ptp1b Inhibitory Assaymentioning
confidence: 99%
“…2, 20.2, 24.0, 29.4, and 36.0 (Figure 2). Mizushina et al (2010) suggested that synthesized docosyl trans-pcoumarate not only inhibited DNA topoisomerase activity and human cancer cell growth, but may function as an anti-cancer agent [9]. Triancontyl p-coumarate from Bombacopsis glabra plays a role as an inhibitor of snake venom metalloproteinase [10].…”
mentioning
confidence: 99%